SCIENTIFIC-METHODICAL APPROACHES TO IN-TEGRAL ESTIMATION OF THE EFFICIENCY OF MARKET REFORMS OF THE RUSSIAN RAILWAYS - A. Zhdanov (Publishing House of the State University of Management, 2017)
The article shows the existing systems of indicators for monitoring the pro-gress and results of the railway reform. All the existing techniques are characterized by great complexity, and the results of the calculations contain a lot of conventions and assumptions, which makes them very approximate. Demands on the methods of evaluating the results of the reforms, taking into account the multidimensionality of the impact of the activities on the state of the industry are justified. It is shown that the system of indicators for the evaluation of reforms should take into account the depth of the impact of events on the economic and social consequences of their realization.